Types of Nursing Intervention on Improving Quality of Life among Patients with Diabetes Mellitus: A Systematic Review - Alam, Agung S.; Samiasih, Amin; Mubin, Mohammad Fatkhul; Pranata, Satriya; Dhamanik, Reina (Current Diabetes Reviews, 2024)
Background: Long-term treatment of patients with diabetes mellitus (DM) is considered a major factor causing disease complications. DM complications mostly impact the patient’s quality of life (QoL). Only a few studies have been conducted summarizing the types of nursing interventions for improving the QoL of DM patients. Objective: The objective of this study is to explore the types of nursing interventions that can improve the QoL of DM patients. Methods: The online databases, including ScienceDirect, Medline, Google Search, and Pro-Quest, were used to search for the relevant articles. Articles that met the inclusion criteria were analyzed, and their level of evidence was determined and synthesized. Results: A total of 30 articles defining the types of nursing intervention on improving the QoL of DM patients were discovered, comprising the five types of nursing interventions, such as health education (15 articles), exercise (8 articles), WhatsApp/short message service (WA/SMS) gateway (3 articles), blood glucose control (3 articles), and black garlic herbal therapy (1 article). Conclusion: Sequentially, the most common types of nursing interventions to improve the QoL of DM patients was health education, followed by exercise, WA/SMS gateway, and glucose control. A personal approach to health education is a significant point in improving the QoL of DM patients in the future. The findings of this study might not be strongly generalized, so further randomized controlled trial (RCT) studies with larger samples are needed.
Keywords: quality of life